IMPLEMENTATION OF PRICE DETERMINATION IN DOWNLOAD MARKET AND MARKET CODIMS RELATED TO THE LAW NO. 5 YEAR 1999 REGARDING MONOPOLY AND PRACTICAL LIMITS BUSINESS COMPETITION IS NOT HEALTHY - ARWENDI, YETTI (Human Sustainability Procedia, 2018)
Problems in the study of how the Implementation of pricing of basic foods in a down market and the market Kodim associated with Law No. 5, 1999, the causes of price discrimination in a down market and the market Kodim, and the legal consequences posed by the price setting. The aim of research to find out how the implementation of pricing of basic foods in a down market and the market Kodim associated with Law No. 5, 1999, the causes of price discrimination, and the legal consequences posed by the price setting. Methods to achieve the goal is to conduct research Sociological Law, ie see how the implementation of the law in society. The results showed the occurrence of discrimination that occurs in a down market with Kodim market for goods groceries. The factors that influence the price discrimination is due to the economic level, the goods are sold in a down market is the luxury goods and imported goods, goods sold in the market more fully below. The legal consequences posed by this discrimination is the effect of monopoly on the welfare of the community, because the monopoly creates injustice, production volume set monopolist is smaller than the volume of output is optimum, suggested to the government to amend this law because of the freedom ofsmall businesses is detrimental to small ruler more. And if not amended advised to make regulations about the setting of this shocked the market